Factors affecting mental wellbeing among UK university students - Aldubaybi, Afnan (2024)
Mental wellbeing is a critical determinant of academic success and overall quality of life among university students (Storrie et al., 2010; Macaskill, 2018). Cognitive function, an integral component of mental health, has been increasingly linked to nutritional status, particularly breakfast consumption patterns (Adolphus et al., 2013; Galioto and Spitznagel, 2016). Concurrently, food insecurity has emerged as a significant concern in higher education settings, with potential ramifications for both nutritional adequacy and mental health outcomes (Bruening et al., 2017; Payne-Sturges et al., 2018). Despite the growing body of research in this field, there remains a paucity of comprehensive studies examining the complex interplay between breakfast consumption, food insecurity, and mental wellbeing among UK university students (Ansari et al., 2015; Macaskill, 2018). This thesis aims to investigate the factors affecting mental wellbeing among UK university students, with a particular focus on the role of breakfast consumption on cognitive function and the impact of food insecurity on mental wellbeing. Through a systematic review, cross-sectional studies, and an intervention study. Our systematic review established a positive association between breakfast consumption and cognitive functions. Cross-sectional studies revealed that skipping breakfast negatively impacted cognitive performance, while food insecurity was prevalent among UK university students and strongly associated with poor mental wellbeing. Financial factors emerged as significant predictors of students' mental health, with those experiencing food insecurity often demonstrating low stress-coping skills. An intervention study focused on enhancing food literacy, financial budgeting, meal preparation, and food waste reduction skills. Results showed improvements in food security status and potential benefits for mental wellbeing, highlighting the effectiveness of educational interventions in addressing these issues. Overall, our findings suggest that multiple factors contribute to students' mental health challenges, including dietary habits, food security status, and financial management skills. This thesis contributes to the understanding of student wellbeing by establishing clear links between breakfast habits, food security, and mental health. It emphasises the need for holistic approaches in university support services, including breakfast programmes, food literacy education, and financial management training. The thesis recommends multi-level strategies involving universities, mental health services, and government regulations to create an environment that fosters both academic success and mental health. Future work will focus on developing and evaluating targeted interventions linking breakfast programmes and food education, considering longitudinal studies and investigations into socioeconomic-specific factors affecting food security and mental wellbeing among UK university students. to reduce food insecurity and potentially alleviate the increasing mental health burden among UK university students. This approach aims to address the complex interplay between nutrition, food security, and mental wellbeing in this vulnerable population. Keywords: mental wellbeing, UK university students, breakfast consumption, food insecurity, cognitive functions, coping strategies.